Efficiency enhancement of dye-sensitized solar cell with PVdF-HFP:MPII:NaI quasi-solid-state electrolyte - Zakaria, P N M; Saaid, F I; Raffi, A A M; Noor, I S M; Woo, H J; Tan, W (IOP Publishing, 2023)
Quasi-solid-state polymer electrolyte (QSSPE) based on poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP) was prepared using sodium iodide (NaI) salt, 1-methyl-3-propylimidazolium iodide (MPII) ionic liquid, propylene carbonate (PC) and 1,2-dimethoxyethane (DME) plasticizers. This paper discusses the effects of using a binary mixture of large (MPII) and small (NaI) cation alkaline salts on enhancing the performance of DSSCs with gel polymer electrolytes. The amount of NaI was varied while the other components were kept constant to study the dependence of dye-sensitized solar cell (DSSC) performance on NaI amount. The incorporation of NaI in PVdF-HFP-MPII-PC-DME has enhanced the efficiency of DSSC. DSSC with 0.6 M MPII and 0.4 M NaI showed the highest efficiency of 4.16 % and short circuit current density (Jsc) of 13.63 mAcm−2. Additionally, the roles of TBP and GuSCN as co-additives in the electrolytes were also discussed in this paper. The presence of 4-tert-butylpyridine (TBP) and guanidine thiocyanate (GuSCN) further enhanced the efficiency from 4.16 to 6.95 %.